ANALYSIS OF THE 2014 JUNIOR HIGH SCHOOL ENGLISH NATIONAL EXAMS BASED ON THE MICRO- AND MACRO-SKILLS ASSESSED - Hady Sutris Winarlim; Agnes Santi Widiati (Widya Mandala Surabaya Catholic University, 2016)
In the past few years, there have been controversial issues regarding the national exams vis-à-vis its legal use as a part of graduation decision, the administration, and the result. The history of the national exam of the elementary and the secondary schools dates back from the late 1960s. Changes of government’s policies concerning the implementation of the national exam and the use of the result should be understood as an effort of the betterment of the education system in Indonesia. Philosophically, the national exam should have the most important characteristics of a test: the validity and accountability. The Ministry of Education and Culture has stipulated that the development and the use of the English National Exam for the junior high school is made in such a way to measure the communicative skill at the functional level in the daily communication which is in line with the goals of the English teaching as contained in framework of the National Examination or Kisi-Kisi Ujian Nasional SMP. This English National Exam consists of 50 multiple choice items covering 45 reading comprehension questions, 3 items of grammar, and 2 items to measure writing skills. As the most items focus on reading comprehension questions, this paper presents the analysis of the questions based on the micro- and macro skills proposed by Brown (2004). The result shows that the levels of the questions tend to be more to measure the macro-skills of reading. As both types of skills are grouped hierarchically, the higher levels of the skills require the manipulation of the lower skills. It is most important for the English teachers to consider this concept when preparing lesson, doing the class activities, especially when guiding students to comprehend texts.